2001
DOI: 10.2739/kurumemedj.48.211
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between Matrix Metalloproteinase 9 and Tissue Inhibitor of Metalloproteinases 1 Expression by Tumor Cells Implicated in Liver Metastasis from Colorectal Carcinoma.

Abstract: Summary:We have evaluated the degree of MMP-9 and TIMP-1 messenger RNA (mRNA) expressions according to cell types in tumor tissues, and evaluated the implication of balance between the MMP-9 mRNA and the TIMP-1 mRNA expression in liver metastasis using orthotopicimplanted colon cancer in nude mouse, and also in 47 patients with colorectal cancer. The grade of MMP-9 or TIMP-1 mRNA expression was classified into 4 categories according to positive cell ratio. A higher grade of MMP-9 mRNA expression in tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Their natural tissue inhibitors (TIMPs) are induced in stromal cells to regulate the proteinase reactions [27]. Increased expression of MMPs and TIMPs plays a key role in CRC invasion and/or metastasis [28]. It was observed that the levels of MMP-9 and TIMP-1 were elevated in CRC patients in relation to healthy controls [7, 16–18].…”
Section: Discussionmentioning
confidence: 99%
“…Their natural tissue inhibitors (TIMPs) are induced in stromal cells to regulate the proteinase reactions [27]. Increased expression of MMPs and TIMPs plays a key role in CRC invasion and/or metastasis [28]. It was observed that the levels of MMP-9 and TIMP-1 were elevated in CRC patients in relation to healthy controls [7, 16–18].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer tissue, however, it is suspected that this balance is disrupted, that MMPs become predominant, and that invasion and metastasis of cancer cells proceeds (13,14). Ogata et al reported that, in experimental and clinical colorectal cancer, the expression of MMP-9 mRNA and TIMP-1 mRNA in tumor cells correlated with liver metastasis, but that there was no relation between the expression of these in stromal cells and liver metastasis (32). These findings suggested that the expression of MMP-9 mRNA and TIMP-1 mRNA in tumor cells is more closely related to the biological behavior of the tumor than is their expression in stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The second is cleavage of the propeptides by other MMPs (N a g a s e et al, 1991; A i m e s , Q u i g l e y , 1995; Anand- Apte et al, 1996;Ogata et al, 2001).…”
Section: Matrix Metalloproteinasementioning
confidence: 99%